Sufism and Its Artistic Creativity: The Role of the Sammāniyya Sufi Order in the Da‘wah Activity in Sumatera - Syafieh Syafieh; Saifuddin Saifuddin; Mawardi Siregar (Teosofi: Jurnal Tasawuf dan Pemikiran Islam, 2021)
This study discusses the Sammāniyya Sufi Order’s creativity in designing art and employing it as a means of da‘wah which emphasizes cultural values and wisdom in a pluralistic society. The informants of this study are the murshid (the Sufi master), caliph, and the adherents of the Sammāniyya Order. The data has been collected from observation, in-depth interviews, focused group discussion, and documentation. This study uses domain analysis and taxonomy to analyze data. The study reveals that the Sammāniyya leaders’ creativity in their da‘wah carried on to the present days has been manifested in the Acehnese saman dance which is related to the practice of the Sammāniyya Order established by Shaykh Muhammad Saman. Debus (the ancient martial art from Banten) and silek kumango (the martial art found in West Sumatera) are also rooted from his practice. Therefore, the arts developed by the shaykh are clear evidence that local wisdom and Islamic Sharia do not have to be contradictory to each other. The arts have become not only an entertainment but also a medium of conveying Islamic messages to the public.